1983
DOI: 10.1161/01.res.52.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of a family of biologically active angiotensin I-like peptides in the dog central nervous system.

Abstract: A family of angiotensin I-like peptides has been derived from endogenous precursors present in dog cerebrospinal fluid after incubation with species homologous renin. These peptides are immunologically and pharmacologically similar to [Ile5]angiotensin I, and have molecular weights ranging between 1300 and 2200 daltons. The presence of precursors in the cerebrospinal fluid able to generate various biologically active angiotensin I-like peptides dissimilar to plasma angiotensin I supports the concept of a local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
10
2
Order By: Relevance
“…Contrary to the findings of Husain et al (1983), we found only one N-terminal dog CSF Aogen structure. Husain et al (1983) presented evidence that a family of biologically active Ang I-like peptides were generated when dog CSF was digested with dog kidney renin; 40% of the Ang I-like material was estimated to be a peptide of higher molecular weight rather than [Ile'l-Ang I. Husain et al (1983) concluded the highmolecular-weight peptides were N-terminally modified and speculated that brain and liver elaborated different forms of Aogen.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the findings of Husain et al (1983), we found only one N-terminal dog CSF Aogen structure. Husain et al (1983) presented evidence that a family of biologically active Ang I-like peptides were generated when dog CSF was digested with dog kidney renin; 40% of the Ang I-like material was estimated to be a peptide of higher molecular weight rather than [Ile'l-Ang I. Husain et al (1983) concluded the highmolecular-weight peptides were N-terminally modified and speculated that brain and liver elaborated different forms of Aogen.…”
Section: Discussioncontrasting
confidence: 99%
“…The discovery of this extended form of Ang I raised our interest since we had previously reported the existence of a family of extended Ang I peptides in the dog’s cerebrospinal fluid [53]. In a series of correlative studies we showed increased expression and content of Ang-(1-12) in the left ventricle of SHR compared with WKY [54].…”
Section: Novel Pathways Upstream From Angiotensin I –The New Research–mentioning
confidence: 99%
“…Of these various lines of evidence, the biochemical findings argue strongly but not conclusively for the existence of an extrarenal isorenin angiotensin system in the brain of mammals, including humans. In this respect, the observations that: 1) brain angiotensinogen shows molecular heterogeneity with respect to the plasma counterpart; 37 2) in the dog, the immunochemical characteristics of the isorenin enzyme are distinct from the enzyme of kidney origin; 3 *-" and 3) extended molecular forms of AI can be formed in the CSF 84 are decisive, but not yet conclusive, steps toward proving the existence of a biosynthetic pathway for the formation of angiotensin peptides in the CNS.…”
Section: Framework To Evaluate Future Researchmentioning
confidence: 99%